2023
DOI: 10.1038/s41380-023-02333-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral organoids with chromosome 21 trisomy secrete Alzheimer’s disease-related soluble aggregates detectable by single-molecule-fluorescence and super-resolution microscopy

Emre Fertan,
Dorothea Böken,
Aoife Murray
et al.

Abstract: Understanding the role of small, soluble aggregates of beta-amyloid (Aβ) and tau in Alzheimer’s disease (AD) is of great importance for the rational design of preventative therapies. Here we report a set of methods for the detection, quantification, and characterisation of soluble aggregates in conditioned media of cerebral organoids derived from human iPSCs with trisomy 21, thus containing an extra copy of the amyloid precursor protein (APP) gene. We detected soluble beta-amyloid (Aβ) and tau aggregates secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…The technique used to quantify soluble aggregates has previously been validated in multiple studies and has been shown to specifically detect aggregates, and not monomers 1719 . It relies on the binding of two copies of the same antibody (6E10, which only has a single epitope 20 ), ensuring that what are detected are at least dimers.…”
Section: Methodsmentioning
confidence: 99%
“…The technique used to quantify soluble aggregates has previously been validated in multiple studies and has been shown to specifically detect aggregates, and not monomers 1719 . It relies on the binding of two copies of the same antibody (6E10, which only has a single epitope 20 ), ensuring that what are detected are at least dimers.…”
Section: Methodsmentioning
confidence: 99%